Access to Sexual and Reproductive Health and Rights Services for Young Women with and Without Disabilities During a Pandemic - Jill Hanass-Hancock; Ayanda Nzuza; Thesandree Padayachee; Kristin Dunkle; Samantha Willan; Mercilene Tanyaradzwa Machisa; Bradley Carpenter (Disabilities)
Young women with and without disabilities in South Africa experience challenges accessing sexual reproductive health and rights (SRHR) services, and this may increase during a crisis. We conducted a longitudinal cohort study with 72 young women with and without disabilities (18–25 years) in eThekwini, South Africa (2020–2022) via a series of in-depth interviews including quantitative and qualitative data on participants’ experiences during the COVID-19 pandemic and access to SRHR. Participants reported that barriers to accessing SRHR services included lockdown regulations, prioritization of COVID-19 at health care facilities, fear of COVID-19 infection, transport challenges, and youth-unfriendly clinics. Participants with disabilities experienced additional barriers to SRHR services, including ongoing (inaccessible services) and pandemic-specific (e.g., masks making lipreading impossible) barriers. Participants reported both non-partner and partner violence, with women with disabilities reporting this more frequently, physical and sexual partner violence, as well as physical and emotional abuse from caregivers. Participants with disabilities were not reporting incidents of violence to caregivers or officials because they had ‘normalized’ the experience of violence, were not believed when trying to disclose, feared that reporting would increase their problems, or could not access services due to disability-related barriers. Inclusive and accessible SRHR information, education, and services are needed. This includes disability-specific staff training, disability audits, and caregiver support and training.